Pelatihan Game Edukasi Android Berbasis HOTS Sebagai Media Evaluasi Pembelajaran - Retno Mustika Dewi; Ni'matush Sholikhah; Muhammad Abdul Ghofur; Ady Soejoto (Universitas Negeri Surabaya, 2020)
The low ability of problem solving and critical thinking is that Indonesian students only master questions with characteristics that are routine and simple, students have not been able to analyze problems that are more complex and problem solving. Evidenced by data from the East Java Education Office as much as 78.88% of the high school and vocational school national exam scores below 55. The purpose of this Community Service Training is to provide training on the preparation of HOTs-based evaluation tools through the use of Android Education games. The dedication partner is MGMP teacher in Magetan Regency. The methods used include lectures, practice, discussion and question and answer. PKM was held on 3 August 2019 at SMAN 3 Magetan attended by 16 participants. The advantages in this Android-based application game, the teacher is not preoccupied in calculating the score of students' learning outcomes because the application can display the value of each student automatically. Teachers do not need to worry about student cheating when implementing this application, because when using the application students must log in first and this application is one application one account. The level of understanding of teachers about the practice of Android-based application games after attending training is 73 out of a score of 100. From the results of the post-test, shows the level of teacher's understanding of the practice of Android-based application games is quite sufficient. Keywords: training, application game based on android